Simulation of a Contact Pseudo-Environment in Calculating Thermal Resistance - Denisenko Alexander (EDP Sciences, 2021)
The use of the temperature criterion in the design of metal-cutting machines, determined on the basis of models that take into account the contact thermal resistances, is an objective necessity. These models should take into account to the maximum extent the actual conditions of contact of parts in the design under consideration, determined by the deviations of the mating surfaces from the ideal shape. The article presents the results of numerical modeling based on the finite element method of the formation of the contact thermal resistance and the evaluation of the influence of the parameters of the intermediate layer (pseudo-environment) that occurs in the contact zone of surfaces with macro-deviations on the passage of the heat flow. The obtained results allowed us to identify the most significant of the considered parameters. It is established that when modeling a pseudo-environment, it is necessary to take into account the coefficient of its thermal conductivity, the size, location and integrity of the actual contact zone.